(untitled) (Journal of Rangpur Medical College, 2022)
Background: Primary open-angle glaucoma (POAG) and atherosclerosis both are fairly common diseases among elderly persons, any adverse changes in serum lipids as a result of glaucoma therapy can increase the risk of coronary heart disease many folds. As topical beta blockers are also widely used and often the first line therapy in many patients requiring treatment for glaucoma for a long time, there is also a possible risk that _-blockers such as timolol adversely affect serum lipid profiles. Objective: The study aimed to evaluate the effect of topical timolol on serum lipid profiles. Methods: This cross-sectional observational study was performed in the department of ophthalmology, Bangabandhu Sheikh Mujib Medical University With convenience type of sampling technique 40 patients with newly diagnosed cases of primary open-angle glaucoma were selected. Baseline fasting lipid profiles were estimated and then timolol maleate 0.5%, 1 drop 12 hourly in both eyes were prescribed. At follow-up after 4 and 12 weeks, again fasting lipid profiles were estimated of the same patients. Results: In this study the baseline mean TC, HDL, LDL & TG were 175.4±19.28 , 46.63±5.33, 104.98±18.49,120.48±28.30 (mg/dl±SD) respectively. Baseline TC/HDL was 3.81±0.06. At follow up after 4 weeks there were increased level of TC, LDL,TG, TC/HDL by 0.45% (P=0.822), 0.8% (P=0.807) 1.82%(P=0.375), and 3.14%(P=0.307) respectively and HDL level decreased by 2.68%(P=0.232). At follow-up, after 12 weeks in comparison to baseline lipid levels, there was an increased level of TC, LDL, TG, and TC/HDL by 0.98% (P=0.959), 3% (P=0.996), 2.8% (P=0.104), and 17.0%(P=0.001) respectively and HDL level decreased by 13.61%(P=0.001). Conclusion: Topical timolol significantly lowers the plasma HDL level. Since the low level of HDL is strongly associated with an increased risk of myocardial infarction, our study cautions against the use of timolol in patients with a previous history of coronary heart disease. J Rang Med Col. September 2022; Vol. 7, No. 2:40-46